2017
DOI: 10.1016/j.parkreldis.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease susceptibility variants and severity of Lewy body pathology

Abstract: Introduction Meta-analyses of genome-wide association studies (GWAS) have established common genetic risk factors for clinical Parkinson’s disease (PD); however, associations between these risk factors and quantitative neuropathologic markers of disease severity have not been well-studied. This study evaluated associations of nominated variants from the most recent PD GWAS meta-analysis with Lewy body disease (LBD) subtype (brainstem, transitional, or diffuse) and pathologic burden of LB pathology as measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…Although the MAPT H1 haplotype is a well‐known genetic risk factor for LBD (PD in particular), studies to date have not indicated that the common MAPT H1 haplotype modifies neuropathological features in individuals with LBD . However, these previous investigations have not taken into account MAPT haplotype diversity, and it is this gap in knowledge that we set out to address in the current study.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Although the MAPT H1 haplotype is a well‐known genetic risk factor for LBD (PD in particular), studies to date have not indicated that the common MAPT H1 haplotype modifies neuropathological features in individuals with LBD . However, these previous investigations have not taken into account MAPT haplotype diversity, and it is this gap in knowledge that we set out to address in the current study.…”
Section: Discussionmentioning
confidence: 89%
“…Although the MAPT H1 haplotype is a well-known genetic risk factor for LBD (PD in particular), studies to date have not indicated that the common MAPT H1 haplotype modifies neuropathological features in individuals with LBD. 13,14 However, these previous investigations have not taken into account MAPT haplotype diversity, and it is this gap in knowledge that we set out to address in the current study. Interestingly, although the H2 haplotype was not notably associated with any of the LBD neuropathological outcomes that were assessed as has been previously shown, 13,14 we observed a significant association between the rare H1j subhaplotype and a greater degree of dorsolateral putaminal dopaminergic degeneration, with a similar (but only nominally significant) association with increased dopaminergic depletion in the ventromedial region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations